Cincinnati Prehospital Stroke Scale (CPSS) as a Screening Tool for Early Identification of Cerebral Large Vessel Occlusions; a Systematic Review and Meta-analysis - Baser, Yazdan; Zarei, Hamed; Gharin, Pantea; Baradaran, Hamid Reza; Sarveazad, Arash; Roshdi Dizaji, Shayan; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2024)
Introduction: Large vessel occlusion (LVO) strokes are associated with worse functional outcomes and higher mortality rates. In the present systematic review and meta-analysis, we evaluated the diagnostic yield of the Cincinnati Prehospital Stroke Scale (CPSS) in detecting LVO. Methods: We performed an extensive systematic search among online databases including Medline, Embase, Web of Science, and Scopus, until July 31st, 2023. We also conducted a manual search on Google and Google scholar, along with citation tracking to supplement the systematic search in retrieving all studies that evaluated the diagnostic accuracy of the CPSS in detecting LVO among patients suspected to stroke. Results: Fourteen studies were included in the present meta-analysis. CPSS showed the sensitivity of 97% (95% CI: 87%–99%) and the specificity of 17% (95% CI: 4%–54%) at the cut-off point of ≥1. The optimal threshold was determined to be ≥2, with a sensitivity of 82% (95% CI: 74%–88%) and specificity of 62% (95% CI: 48%–74%) in detecting LVO. At the highest cut-off point of ≥3, the CPSS had the lowest sensitivity of 60% (95% CI: 51%–69%) and the highest specificity of 81% (95% CI: 71%–88%). Sensitivity analyses showed the robustness of the results regardless of study population, inclusion of hemorrhagic stroke patients, pre-hospital or in-hospital settings, and the definition of LVO. Conclusion: A very low level of evidence demonstrated that CPSS, with a threshold set at ≥2, is a useful tool for identifying LVO stroke and directing patients to CSCs, both in prehospital and in-hospital settings.